Gender as Innovative Scientific and Philosophical Discourse - E. E. Shishlova (Vestnik MGIMO-Universiteta, 2013)
The author analyses actual problems of gender discourse, such as gender socialization and gender identification from positions of the leading social theories of the 20th century (structural-functional, constructivist and structural-constructivist), denoting change of classical thinking by modern and postmodern.